Targeting multiple oncogenic pathways for the treatment of hepatocellular carcinoma - Swamy, S.; Kameshwar, V.; Shubha, P.; Looi, C.; Shanmugam, M.; Arfuso, Frank; Dharmarajan, Arunasalam; Sethi, Gautam; Shivananju, N.; Bishayee, A. (2016)
Hepatocellular carcinoma (HCC) is one of the most common forms of liver cancer diagnosed worldwide. HCC occurs due to chronic liver disease and is often diagnosed at advanced stages. Chemotherapeutic agents such as doxorubicin are currently used as first-line agents for HCC therapy, but these are non-selective cytotoxic molecules with significant side effects. Sorafenib, a multi-targeted tyrosine kinase inhibitor, is the only approved targeted drug for HCC patients. However, due to adverse side effects and limited efficacy, there is a need for the identification of novel pharmacological drugs beyond sorafenib. Several agents that target and inhibit various signaling pathways involved in HCC are currently being assessed for HCC treatment. In the present review article, we summarize the diverse signal transduction pathways responsible for initiation as well as progression of HCC and also the potential anticancer effects of selected targeted therapies that can be employed for HCC therapy.